Avaliação de diferentes formulações de azul de metileno na terapia fotodinâmica em doença periodontal induzida em ratos - Pasini, Marcela Mozzaquatro (2014)
This study aimed to evaluate the histological effect of different formulations of Methylene Blue (MB) used in antimicrobial Photodynamic Therapy (aPDT) as adjuvant to conventional treatment, on gingival collagen fibers in the treatment of periodontal disease induced in rats. In this study were used 120 male rats (Rattus Novergicus, Wistar lineage). The periodontitis was induced by placing a ligature on right mandibular first molar in 105 rats. After 7 days, they were removed and the animals were randomized in 5 groups: NC negative control; PC positive control (no treatment); SRP - scaling and root planning (SRP) and periodontal pocket irrigation with saline solution; aPDT SRP + aPDT (with MB 0,01% dissolved in water + laser); aPDT/ethanol SRP + aPDT (with MB 0,01% dissolved in solvents containing ethanol 20% + laser). The NC animals received neither periodontitis induction nor treatment. Five animals of NC and PC and ten animals of SRP, aPDT and aPDT/ethanol are euthanized 7, 15 and 30 days after treatment. Gingival samples were collected to the quantification of collagen fibers and descriptive analysis of collagen type I and III proportion and organization. Data were analyzed with ANOVA and multilevel Poisson regression analysis. The animals of NC, PC, SRP, aPDT and aPDT/ethanol showed percentage of collagen fibers area of 67,99%, 45,71%, 58,39%, 71,70% and 72,37%, respectively, but no statistical difference was seen in aPDT and aPDT/ethanol; the collagen fibers area was higher at 30 days (71,37%) than at 7 days (60,25%) and at 15 days (63,12%) after treatment, showing statistical difference only at 30 days (ANOVA). Considering multivariate Poisson regression analysis, aPDT and aPDT/ethanol showed 6% higher rate of collagen fibers organization when compared to NC (p<0,05); this organization increased 5% at 15 days after treatment and 19% at 30 days when compared to 7 days (p<0,05). The action of different formulations of MB was similar concerning the quantity and organization of gingival collagen fibers, presenting higher collagen type I quantity, parallel and dense alignment at 30 days after treatment. According to the experimental model used in this study, the ethanol presence in MB formulation doesn t interfere on collagen fibers quantity and quality of collagen fibers in periodontal wound healing. This study suggests the aPDT could be a promising alternative to periodontal disease treatment as adjuvant to conventional treatment.